Temporal variability of explosive activity at Tajogaite volcano, Cumbre Vieja (Canary Islands), 2021 eruption from ground-based infrared photography and videography - Birnbaum, Janine; Lev, Einat; Hernandez, Pedro A.; Barrancos, José; Padilla, Germán D.; Asensio-Ramos, María; Calvo, David; Rodríguez, Fátima; Pérez, Nemesio M.; D’Auria, Luca; Calvari, Sonia (Frontiers in Earth Science, 2023)
The 2021 eruption at Tajogaite (Cumbre Vieja) volcano (La Palma, Spain) was characterized by Strombolian eruptions, Hawaiian fountaining, white gas-dominated and grey ash-rich plumes, and lava effusion from multiple vents. The eruption dynamics were recorded using ground-based thermal photography and videography. We show results from the analysis of short (<5 min) near-daily thermal videos taken throughout the eruption from multiple ground-based locations and continuous time-lapse thermal photos over the period November 16 to November 26. We measure the apparent radius, velocity, and volume flux of the high-temperature gas-and-ash jet and lava fountaining behaviors to investigate the evolution of the explosive activity over multiple time scales (seconds-minutes, hours, and days-weeks). We find fluctuations in volume flux of explosive material that correlate with changes in volcanic tremor and hours-long increases in explosive flux that are immediately preceded by increases in lava effusion rate. Correlated behavior at multiple vents suggests dynamic magma ascent pathways connected in the shallow (tens to hundreds of meters) sub-surface.